Distribution of trace metals in pore water along Terengganu beach - Rahman, Md. Mokhlesur; Fikhria, A.F.; Yunus, Kamaruzzaman; Wan Nik, W.B. (INSI Publications, 2012)
The aim of this paper was to analyze some trace metal concentrations (Cd, Cu, Al, Pb and Zn) in pore water along Terengganu beach. The samples were extracted by using the APDC-MIBK solvent extraction technique and analyzed by ICP-MS. The results showed that the range of trace metal concentration in pore water for Cd, Cu, Al, Pb and Zn were 0.01 μg L-1, -0.26 μg L-1, 0.65 μg L-1, 5.01 μg L-1, 1.70 μg L-1, -28.9 μg L-1, 0.37 μg L-1, -10.5 μg L-1, 7.66 μg L-1, -271 μg L-1, respectively. In overall, trace metal concentration in pore water does not reaching the limit of Department of Environment DOE) and it is still under safety level where there are no anthropogenic effects.